PHYSICAL-CHEMICAL PRINCIPLES OF THE PREPARATION OF HYBRID MATERIALS ON THE BASIS OF DETONATION NANODIAMONDS AS A NEW GENERATION DRUG DELIVERY SYSTEMS AND THEIR PROPERTIES - R. Y. Yakovlev; I. I. Kulakova; G. A. Badun; G. V. Lisichkin; A. V. Valueva; N. G. Selezenev; N. B. Leonidov (Разработка и регистрация лекарственных средств)
There were illustrated the main questions of development of new generation drug delivery systems as hybrid nanomaterials as follows: selection of nanocarrier, its standardization and the methods of immobilization of biologically active and medicinal substances. The basic organs of distribution and accumulation of advanced carbon nanocarrier - detonation nanodiamond were identified. It was shown that antihypoxic effect of the nanodiamond-glycine conjugate increased in comparison with a native Glycine and Mexidolum® as reference drugs.